The effect of plants on the energy output of green roof photovoltaic systems in tropical climates - Kaewpraek C.; Ali L.; Rahman M.A.; Shakeri M.; Chowdhury M.S.; Jamal M.S.; Mia M.S.; Pasupuleti J.; Dong L.K.; Techato K. (MDPI AG, 2023)
alternative energy; carbon dioxide; climate change; energy efficiency; fossil fuel; global climate; photovoltaic system; roof; solar power; tropical region; Songkhla; Southern Region; Thailand